2022
DOI: 10.21037/atm-21-7043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed and methylated genes and construction of a co-expression network in age-related macular degeneration

Abstract: Background: Age-related macular degeneration (AMD) is the leading cause of blindness for people over 50 years old worldwide. The purpose of this study was to identify differentially expressed and methylated genes (DEMGs) and construct a co-expression network for AMD.Methods: Microarray expression (GSE29801 dataset) and DNA methylation (GSE102952 dataset) profiles were retrieved from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) and differentially methylated genes (DMGs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Among these genes, activation of ERK1 /2 and CREB showed protection function for human RPEs from H 2 O 2 -induced oxidative damage ( 36 ). AR was proved to be a hub gene during the pathogenesis of AMD ( 37 ). These results provide further insights into the biological processes and potential roles regulated by the 12 hub genes.…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, activation of ERK1 /2 and CREB showed protection function for human RPEs from H 2 O 2 -induced oxidative damage ( 36 ). AR was proved to be a hub gene during the pathogenesis of AMD ( 37 ). These results provide further insights into the biological processes and potential roles regulated by the 12 hub genes.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the expression of FSTL1 was higher in AMD compared to the normal control group. Niu et al also investigated the potential involvement of FSTL1 in the pathogenesis of PDR by analyzing vitreous uid and proliferative membrane samples from PDR patients 30,31 . These ndings align with our results.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed the gene expression of genes in the RPE/choroid tissues, aiming to identify hub genes in AMD patients. In contrast to previous research ( Li et al, 2022 ; Liang et al, 2022 ; Wang et al, 2022 ), our approach utilized three gene expression profiles comprising 55 AMD samples and 138 control samples. Two of these datasets were used to identify DEGs, whereas the third dataset was used to analyze key gene network modules through the WGCNA.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic network analyses based on gene expression profiles can assist in identifying key genes and disease-related pathways. Traditional analyses of AMD have focused primarily on differentially expressed genes (DEGs), with limited knowledge regarding their co-expression patterns ( Li et al, 2022 ; Liang et al, 2022 ; Wang et al, 2022 ). Weighted gene co-expression network analysis (WGCNA) has been widely used to explore key modules and hub genes for the identification of candidate biomarkers and therapeutic targets in diseases like cancers and neuropsychiatric disorders ( Li et al, 2018 ; Jo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation